Exoticism in the products of art education students according to psychoanalytic theory - Mohsen, Hamza Sadiq; AbdelKarim, Mohammad Saadi (Al-Adab Journal, 2021)
The products of the students of the Art Education Department showed a Strangeness tendency as a result of the changes that occurred in the thought, as this change played an important role in the learner’s vision, which reflected on his artistic product, and he created new aesthetic standards, by adding strangeness to things to gain a new aesthetic connotation, so the exploratory study, which conducted by The researcher on these products, and noted that most of the students tend to break the familiar and employ the Strangeness in their products, which formed an indication based on the jurisprudence of his research problem.The research consisted of four chapters according to the following: The first chapter included a presentation of the research problem and the importance of this research. The research goal is determined. The limits of the research and then the definition of the most important terms mentioned in the title and body of the research. The second chapter contained the theoretical framework which presented in the first topic the Strangeness and its intellectual and philosophical premises, and the second topic concerned with the theory of psychological analysis its fundamentals and its premises.The third chapter: The research methodology (content analysis) and society, which are among the products of art education students in the drawing material, which amounted to (77) artistic products. An intentional sample was represented in. To complete the analysis of the samples, the researcher built the research instrument according to the literature and previous studiesThe fourth chapter contains the results, conclusions, recommendations, and suggestions that the researcher reached after analyzing the sample.